Neural correlates of tinnitus duration and Distress: A positron emission tomography study. Issue 1 (22nd October 2011) - Schecklmann, Martin; Landgrebe, Michael; Poeppl, Timm B.; Kreuzer, Peter; Männer, Peter; Marienhagen, Jörg; Wack, David S.; Kleinjung, Tobias; Hajak, Göran; Langguth, Berthold
Abstract Cerebral 18F‐deoxyglucose positron emission tomography (FDG‐PET) has shown altered auditory pathway activity in tinnitus. However, the corresponding studies involved only small samples and analyses were restricted to the auditory cortex in most studies. Evidence is growing that also limbic, frontal, and parietal areas are involved in the pathophysiology of chronic tinnitus. These regions are considered to mediate perceptual, attentional, and emotional processes. Thus, the aim of the present study was the systematic evaluation of metabolic brain activity in a large sample of tinnitus patients. Ninety one patients with chronic tinnitus underwent FDG‐PET. The effects of tinnitus severity (assessed by a tinnitus questionnaire score), duration and laterality were evaluated with statistical parametric mapping (SPM) in whole brain analyses. In addition, region of interest analyses were performed for primary auditory areas. Tinnitus duration correlated positively with brain metabolism in right inferior frontal, right ventro‐medial prefrontal, and right posterior cingulate cortex. Tinnitus distress correlated positively with activation of left and right posterior inferior temporal gyrus as well as left and right posterior parahippocampal–hippocampal interface. Region of interest analysis demonstrated an overactivation of left in contrast to right Heschl's gyrus independently from tinnitus laterality and anatomical hemispheric differences. Tinnitus duration and distress were associated with areas involved in attentional and emotional processing. This is in line with recent findings indicating the relevance of higher order areas in the pathophysiology of tinnitus. Earlier results of asymmetric activation of the auditory cortices in tinnitus were confirmed, i.e., left‐sided overactivation was found independently from tinnitus laterality. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.